The contribution made by Sytenko M.I. to the development of prosthetic-orthopaedic aid to population - Korzh, Mykola; Yaremenko, Dmytro; Korolkov, Oleksandr; Shevchenko, Olena; Golubeva, Inna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article gives a brief account of the biography of an outstanding orthopaedist-traumatologist, an organizer of health protection, Professor M.I. Sytenko, describes his views on the significance of prosthetic-orthopaedic aid and rehabilitation, and elucidates his part in the formation and development of these kinds of aid to the population of Ukraine.